PERUBAHAN NILAI BUDAYA MINANGKABAU DALAM NOVEL TENGGELAMNYA KAPAL VAN DER WIJCK KARYA HAMKA DAN NOVEL BULAN SUSUT KARYA ISMET FANANY (KAJIAN PERBANDINGAN) - Pebriani, Yulia (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
Local culture is very diverse Indonesia became an honor and challenge to maintain and inherited to the next generation. Local Indonesian culture is very proud because it has a very varied diversity and unique. As time, lead to changes in lifestyle a more modern society. As a result, people will prefer the new culture that may be considered more practical than the local culture. Views on kinship, treasures, and wander in the novel Tenggelamnya Kapal Van Der Wijck Hamka works and novels Bulan Susut works Ismet Fanany changes and cultural shifts. Kinship, treasures, and wander in the novel Sinking Ship Van Der Wijck Hamka's work is described explicitly, whereas kinship, treasures, and wander in the novel Month Losses Ismet work Fanany described implicitly. Changes in people's lives has implications for social Minangkabau culture in Minangkabau society. A leadership that is both functional mamak transformed into symbolic leadership. Mamak originally as straps tribesmen, has changed the status and intrinsic meaning.